The Growth of Shoot Cutting of Ant-nest Plant (Myrmecodia pendens Merr. & L.M. Perry) that Planted in Various Planting Medium - Suci Rahmadani Putri; Suwirmen Suwirmen; Zozy Aneloi Noli (Universitas Andalas, 2019)
The research about The Growth of Shoot Cutting of Ant-nest Plant (Myrmecodia pendens Merr. & L.M. Perry) that Planted in various planting medium was held from May until August 2018 in Greenhouse and Plant Physiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Science, Andalas University, Padang. The aim of this research was to find out the effects of various planting medium to the growth of shoot cutting Ant-nest Plant. This research used Completely Randomized Design (CRD) with five treatments (sand, husk charcoal, media moss, coconut fiber and fern’s root) and six replications. The results showed that shoot cutting that planted in sand, husk charcoal and fern had a highest life percentage (100%). Shoot cutting that planted in coconut fiber showed a highest height accretion. Shoot cutting that planted in media moss showed the highest root amount, longest root length and containing clorophyl level.